Crowdsourcing health communication about condom use in men who have sex with men in China: a randomised controlled trial. (October 2016) - Tang, Weiming; Mao, Jessica; Liu, Chuncheng; Mollan, Katie; Li, Haochu; Wong, Terrence; Zhang, Ye; Tang, Songyuan; Hudgens, Michael; Qin, Yilu; Ma, Baoli; Liao, Meizhen; et al.
Abstract: Background: The Chinese government now encourages innovation, and more specifically, crowdsourcing. Crowdsourcing, the process of shifting individual tasks to a large group, might reimagine health communication, making it more people-centred. We aimed to compare the effectiveness of a crowdsourced versus social marketing condom promotion video to promote condom use. Methods: A non-inferiority randomised controlled trial was conducted in November 2015 in China. Men who have sex with men (MSM) aged 16 years or older who reported having had sexual contact without use of a condom in the preceding 3 months were recruited through a nationwide MSM website. Men were randomly allocated to one of the two arms in a 1:1 ratio using a computer algorithm and then watched one of two videos. The crowdsourced video was developed through an open contest and the social marketing video was designed by a company. Participants completed a baseline survey and follow-up surveys at 3 weeks and 3 months post-intervention. The primary outcome was incidence of sexual contact without a condom. Intention-to-treat analysis was used, with a non-inferiority margin of 10%. The trial is registered withClinicalTrials.gov, numberNCT02516930 . All participants gave informed consent and the protocol was approved by Chinese (Guangdong Provincial Centre for Skin Diseases and STI Control) and American (University of North Carolina at Chapel Hill and the University of California San Francisco) institutional review boards. Findings: 1173 participants were recruited to the study; 907 (77%) completed the 3-week follow up and 791 (67%) the three-month follow up. At three weeks, 146/434 (33·6%) participants in the crowdsourced group and 153/473 (32·3%) in the social marketing group reported having sexual contact without a condom. The crowdsourced intervention achieved our pre-specified non-inferiority criterion (estimated difference: +1·3% [95%CI: 4·8–7·4]). At 3 months, 196/376 (52·1%) men in the crowdsourced group and 206/415 (49·6%) in the social-marketing group reported having sexual contact without a condom (estimated difference: +2·5% [95%CI −4·5–9·5%]). The two groups reported similar HIV testing rates and other condom-related secondary outcomes. The cost of the crowdsourcing intervention was substantially lower than the social marketing intervention (16 686 vs 26 845 USD). No adverse outcomes were reported. Interpretation: Crowdsourcing could be a useful tool in China, which has a large population and government support. Crowdsourcing provides a structured system for multi-sectoral input into health policy in China. Funding: US National Institute of Allergy and Infectious Diseases (NIAID; 1R01AI114310); University of North Carolina (UNC)-South China Sexually Transmitted Disease Research Training Centre (Fogarty International Centre; 1D43TW009532); UNC Center for AIDS Research (NIAID; 5P30AI050410); University of California San Francisco Centre for AIDS Research (NIAID; P30 AI027763); US National Institute of Mental Health (R00MH093201 to CW); UNC Chapel Hill, Johns Hopkins University, Morehead School of Medicine and Tulane University (UJMT) Fogarty Fellowship (FIC R25TW0093); Doris Duke International Clinical Research Fellowship; US National Center for Advancing Translational Sciences (UL1TR001111).